A novel hierarchical energy management of a renewable microgrid considering static and dynamic frequency - Rezaei, Navid; Kalantar, Mohsen (Journal of renewable and sustainable energy, 2015)
The present paper addresses a novel energy management system to efficiently procure the frequency security requirements of an islanded microgrid. The static and dynamic behaviors of the microgrid frequency are modeled based on the droop control and virtual inertia concepts. Two novel frequency dependent indices are formulated and controlled via a centralized hierarchical energy management system. The main objective of the paper is to optimize the microgrid frequency security and also the rate of change of frequency indices by providing a sustainable strategy for managing the energy and reserve resources. It is aimed to schedule the daily primary and secondary frequency control reserves such that security is ensured subject to the techno-economic restrictions. The derived formulation is solved using a mixed integer linear programming approach regarding the comprehensive operational constraints of the microgrids which ensures the system sustainability. Meanwhile, an efficient scenario-based stochastic programming methodology is employed to precisely managing the reserve resources against the system uncertainties. The simulation results are implemented in a typical microgrid and investigated over a 24 h time horizon. Analyzing the results verifies the significance of the frequency modeling in the precise scheduling of the microgrid energy and ancillary service requirements.